Reproducibility of the 6-Min Step Test in Subjects With COPD - Munari, Anelise Bauer; Silva, Isabela Julia Cristiana Santos; Gulart, Aline Almeida; Venâncio, Raysa Silva; Klein, Suelen Roberta; Zanotto, Júlia; Mayer, Anamaria Fleig (Respiratory care, 2021)
Test-retest reproducibility of the 6-min step test (6MST) is controversial in patients with COPD because the decision to perform a second test is influenced by interruptions, physiological overload, and the patient's exercise tolerance. The aim of this study was to analyze the reproducibility of performance on the 6MST (ie, number of steps climbed and interruptions) and physiological variables in subjects with COPD, with and without poor exercise tolerance, and with and without interruptions during the test. Subjects performed 2 6MST (6MST , 6MST ) with a minimum of 30 min rest between tests. Physiological variables were assessed with a gas analyzer. Subjects who performed ≤ 78 steps in the 6MST and ≤ 86 steps in the test with the higher number of steps performed (6MST ) were considered to have poor exercise tolerance. Subjects were also stratified according to those who interrupted the 6MST and those who did not interrupt the 6MST . 40 subjects (31 men; FEV percent of predicted = 50.4 ± 13.5) participated in the study. The number of steps, interruptions, and physiological variables showed moderate to high reliability (intraclass correlation coefficient: 0.70-0.99, < .001). Thirty-one (77.5%) subjects had a better performance during 6MST than 6MST (mean difference: 4.65 ± 5.59, < .001). Although the number of times subjects were interrupted was similar between the 2 tests ( = .66), the duration of these interruptions was shorter during 6MST (mean difference: -0.12 ± 0.39 s, = .040). The difference in the number of steps (6MST - 6MST ) did not differ between subjects who performed ≤78 steps (mean difference: 5.64 ± 5.32 steps; 10.3%; < 0.001) and ≥ 79 steps (3.00 ± 5.82 steps; 6.13%; = 0.08) on the 6MST ( = 0.15) and between subjects who performed ≤ 86 steps (5.39 ± 5.14 steps; 9.39%; < 0.001) and ≥ 87 steps (2.92 ± 6.43 steps; 2.74%; = 0.14) steps on the 6MST ( = 0.20). Performance and physiological variables in the 6MST were reproducible, and a second test did not impose greater physiological overload. Two tests were essential for patients with poor exercise tolerance.